Proliferating Trichilemmal Cysts of the Scalp on CT - Chang, S.J. (AJNR Am J Neuroradiol, 2006)
SUMMARY: Proliferating trichilemmal cysts, also known as pilar tumors, are slow-growing lobulated masses most commonly found on the scalp of elderly women. We present the case of a 69-year-old woman with a 25-year history of multiple enlarging scalp masses. The patient was evaluated for surgical consultation after the dominant mass presented with malignant degeneration. A CT of the head revealed multiple large, subcutaneous, cystic masses with calcifications.